(3n+10) chia het (n-1)
(3n-3+13) chia het (n-1)
3(n-1) +13 chia het n-1
13 chia hết n-1
n-1 thuộc Ư(13)={1;13}
n thuộc {2.14}
3n + 10 ⋮ n - 1 <=> 3 ( n - 1 ) + 13 ⋮ n - 1
=> 13 ⋮ n - 1 hay n - 1 thuộc ước của 13
ước của 13 là - 13 ; - 1 ; 1 ; 13
=> n - 1 = { - 13 ; - 1 ; 1 ; 3 }
=> n = { - 12 ; 0 ; 2 ; 4 }
Giải:
Ta có:
3n + 10 chia hết cho n - 1
=> ( 3n - 3 ) + 13 chia hết cho n - 1
=> 3 ( n - 1 ) + 13 chia chết cho n - 1
=> 13 chia hết cho n - 1
\(\Rightarrow n-1\in\left\{1;13;\right\}\)
\(\Rightarrow n\in\left\{2;14\right\}\)
Vậy \(n\in\left\{2;14\right\}\)